Design for longevity in industrial products: A pedagogical case study on steel moulds for injection mould manufacturing - Folkmann, Emilie B.; Ricard, Lykke Margot (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper aims to demonstrate the life cycle costing and environmental impacts of different R-strategy scenarios, with a focus on steel moulds. Reuse primarily focuses on remanufacturing steel moulds and exploring the most environmentally optimal strategy, serving as a supplier in a circular economy. The scope of this case study does not include recycling scenarios. The study uses a pedagogical case study in collaboration with The LEGO Group. One approach is to map the CO2-eq footprint of steel mould consumption to prepare for a digital architecture based on material consumption and circular strategies.